Simulation of Street Furniture Models with Hostile Architecture (Study of Dago Street) - Subagdja, Lingga Areal; Pratama, Alldi Eka; Putri, Tika Novis (Rumoh Journal of Architecture, 2025)
Hostile Architecture is a public space design strategy that aims to shape and control social behavior by preventing certain activities that are considered undesirable, such as sleeping in public places, staying too long in one spot, or gathering in large groups. This approach is often applied subtly through design elements such as street furniture that are intentionally designed to reduce comfort or accessibility in order to prevent misuse of space. One area that often experiences undesirable behavior is the pedestrian sidewalk along Jalan Dago, Bandung. This area, although it has high pedestrian activity, is also vulnerable to problems such as vandalism, crime, and other non-productive activities. This study chose Jalan Dago as a case study because its physical and social context is considered suitable for the application of Hostile Architecture design strategies. The main objective of this study is to develop a street furniture design model with Hostile Architecture principles to improve security, order, and social control in public spaces. The research method used in this design is a qualitative design-based approach, through participatory observation, field documentation, and literature studies related to user behavior and public space design. The analysis will focus on how specific elements—such as slanted benches, armrests, glaring lighting, and surface modifications—can discourage deviant behavior without completely eliminating the function of the space. The results of the study have shown that the characteristics of Jalan Dago can support the application of Hostile Architecture through appropriate design to the context. Therefore, several street furniture models are proposed to minimize the potential for negative activities, while creating a safer, more comfortable, orderly, and inclusive public space for its users.